Prescription Patterns of Asthma Preventers Among Children and Adolescents Between Australia and South Korea - Seo, Min Sook; Hillen, Jodie; Kang, Dong Yoon; Pratt, Nicole; Shin, Ju-Young (Frontiers in Pharmacology, 2022)
ABSTRACT Purpose: Inhaled Corticosteroids (ICSs) and oral Leukotriene Receptor Antagonists (LTRAs) are commonly prescribed asthma preventers, however, concerns have been raised as to whether montelukast (LTRA) is associated with an increase in occurrences of neuropsychiatric side effects in children. Our study was conducted to observe prescribing patterns of asthma preventers among paediatric patients specifically focusing on ICSs and LTRAs between Australia and South Korea to see intercountry differences in the use of these medicines. Materials and Methods: The Health Insurance Review and Assessment Paediatric Patients Sample dataset for South Korea and data provided by Services Australia were used in the study. Paediatric patients aged between 3 and 19 with more than one dispensing of an asthma preventer and at least one reliever between Jan 1, 2018 and December 31, 2018 were selected. Prevalence per 100,000 persons and standardised prevalence were estimated. Results: A total of 358,470 patients (204,270 from South Korea and 154,200 from Australia) were included in the study. A higher prevalence of ICS-based inhalers was seen in Australia with 80.1% compared to 13.5% in South Korea. In contrast, use of LTRAs was more prevalent in South Korea with 57.6% while in Australia, montelukast was the only LTRA dispensed at a proportion of 18.9%. Conclusion: Australia showed a tendency of prescribing ICS-based preventers whereas South Korea exhibited a preference towards the oral LTRAs. Given the potential risk of neuropsychiatric side effects among paediatric patients with montelukast, reasons for the high use of montelukast in South Korea should be investigated further.